Behavior of Using Plastic Containers as Food and Beverage Packaging in the Working Area of Kampung Baru Health Center Medan Maimun - Simanjuntak, Emma DN; Tua, Mindo; Tarigan, Frida L (Proceeding - Sari Mutiara Indonesia International Conference on Health, 2018)
Now a days Plastic Containers are increasingly using as food and beverage packaging by the people. Food and drinks we consume are almost always connected to plastic, from being sold in markets or supermarkets, we bring it home, until we process and store. In the process there is a transferring of chemicals from plastic packaging to foods and beverages that are at risk for health problems such as resulting in an increased risk of heart disease, cancer, brain disorders. Basically, there is no one type of plastic that is really safe to use. We must be careful while choosing and using plastic packaging that we use everyday. Qualitative research with phenomenological approach about the behavior of using plastic containers as food and baverage packaging with 7 respondents, namely 3 working women, 4 health workers. From the results of the research through in-depth interviews all respondents did not know about the numeric code and BPA Free on the packaging Plastic. All respondents chose plastic containers only because of the price and brand. Likewise, reactions in using plastic containers as food and beverage packaging, most of respondents immediately put food and hot drinks into plastic containers. Needed by the government to provide information regarding the use of plastic containers that are safe to use and announcement of using plastic containers can affect to the health and to the environment.